A Case Report: Severe Chronic Obstructive Pulmonary Disease (COPD) Exacerbation Due To Community-Acquired Pneumonia (CAP) Infection In Smokers - Mustofa, Syazili; Anggraeni, Liza; Putri, Giska Tri; Kurniawan, Betta; Agung Kurnia, Ahmad Fadila (Jurnal Ilmu Kedokteran dan Kesehatan, 2025)
COPD, also know as Chronic Obstructive Pulmonary Disease, refers to a lung condition marked by persistent and progressive airflow blockage. This is usually the result of a chronic inflammatory reaction in the respiratory tract brought on by exposure to harmful gases or particles. Respiratory tract infections like Community-Acquired Pneumonia (CAP) frequently cause COPD exacerbations, while smoking is the main risk factor that contributes to the onset and worsening of COPD. The goal of this case report is to provide an understanding of the underlying mechanism of severe COPD cause by CAP infection in smokers and to diagnose and manage the condition effectively. A 72-year-old man complained of shortness of breath that he had been having for the last year, and that had worsened over the previous three days when he arrived at the emergency unit of Abdoel Moeloek Hospital in Lampung. In addition, he also had a fever and severe cough with yellow sputum. Following a comprehensive review of medical history, physical examination, and supporting examination, it was concluded that a CAP infection was linked to severe COPD exacerbation. The patient received antibiotic medication and hospitalization treatment for symptomatic therapy.